The interaction between cigarette smoking on the incidence of hypertension among adolescents - Hidayat, Tin Kumalasari; Herawati, Vitri Dyah; Suwarni, Anik (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2025)
Background: Hypertension is a non-communicable disease known as the